2004
DOI: 10.3758/bf03196862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiplication practice on product verification: Integrated structures model or retrieval-induced forgetting?

Abstract: 324Manly and Spoehr (1999) proposed the integrated structures model (ISM) of multiplication fact representation. According to the ISM, multiplication problems activate three distinct representations in memory: a whole facts representation (e.g., 2 3 7 5 14), an analog code representing the approximate magnitude of the product, and an operand multiples representation consisting of the multiples of the problems operands (e.g., 2 3 7 5 14 activates the operand multiples of 2, 4, 6, 8, . . . and 7, 14, 21, 28 . . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…The finding has proven to be highly robust and general, emerging in many contexts and with a variety of materials (e.g., with factual propositions, M. C. Anderson & Bell, 2001;Gómez-Ariza, Lechuga, Pelegrina, & Bajo, 2005;Macrae & MacLeod, 1999;phonological categories, Bajo, Gómez-Ariza, Fernandez, & Marful, 2006;text passages, Carroll, Campbell-Ratcliffe, Murnane, & Perfect, 2007;Chan, McDermott, & Roediger, 2006;Little, Storm, & Bjork, 2011;visuospatial materials, Ciranni & Shimamura, 1999; language selection, Levy, McVeigh, Marful, & Anderson, 2007; arithmetic facts, Phenix & Campbell, 2004; eyewitness memory, Garcia-Bajos, Migueles, & Anderson, 2009;M. D. MacLeod, 2002;Saunders & MacLeod, 2002;Shaw, Bjork, & Handal, 1995;mental imagery, Saunders, Fernandes, & Kosnes, 2009; creative problem solving, Storm, Angello, & Bjork, 2011;autobiographical memory, Barnier, Hung, & Conway, 2004;and social contexts, Dunn & Spellman, 2003;Storm, Bjork, & Bjork, 2005).…”
Section: The Problemmentioning
confidence: 99%
“…The finding has proven to be highly robust and general, emerging in many contexts and with a variety of materials (e.g., with factual propositions, M. C. Anderson & Bell, 2001;Gómez-Ariza, Lechuga, Pelegrina, & Bajo, 2005;Macrae & MacLeod, 1999;phonological categories, Bajo, Gómez-Ariza, Fernandez, & Marful, 2006;text passages, Carroll, Campbell-Ratcliffe, Murnane, & Perfect, 2007;Chan, McDermott, & Roediger, 2006;Little, Storm, & Bjork, 2011;visuospatial materials, Ciranni & Shimamura, 1999; language selection, Levy, McVeigh, Marful, & Anderson, 2007; arithmetic facts, Phenix & Campbell, 2004; eyewitness memory, Garcia-Bajos, Migueles, & Anderson, 2009;M. D. MacLeod, 2002;Saunders & MacLeod, 2002;Shaw, Bjork, & Handal, 1995;mental imagery, Saunders, Fernandes, & Kosnes, 2009; creative problem solving, Storm, Angello, & Bjork, 2011;autobiographical memory, Barnier, Hung, & Conway, 2004;and social contexts, Dunn & Spellman, 2003;Storm, Bjork, & Bjork, 2005).…”
Section: The Problemmentioning
confidence: 99%
“…One of these concerns how problems are functionally related to each other in memory and how the network of related facts is processed (i.e., specific assumptions about excitatory and inhibitory processes). The IE model leads one to think of each arithmetic fact as an isolated entity, but it is well established that processing one problem has effects on other, related problems (Ashcraft, 1992(Ashcraft, , 1995Campbell, 1987Campbell, , 1997Campbell & Timm, 2000;Manly & Spoehr, 1999;Phenix & Campbell, 2004). For example, Phenix and Campbell demonstrated that repeatedly practicing a multiplication problem facilitated retrieval of the correct product, as was expected, but also reduced the accessibility of other multiples of the factors.…”
Section: Future Directions For the Identical Elements Modelmentioning
confidence: 99%
“…To focus retrieval on the target, inhibition is thought to suppress competing traces, with the lingering effects causing difficulties in recalling those competitors. This phenomenon, known as retrieval-induced forgetting (RIF), has been observed in many contexts, including episodic memory (e.g., Anderson, Bjork, & Bjork, 1994;Ciranni & Shimamura, 1999), semantic memory (Blaxton & Neely, 1983;Johnson & Anderson, 2004), memory for word meaning (Johnson & Anderson, 2004;Shivde & Anderson, 2001), memory for factual knowledge (Anderson & Bell, 2001;Gómez-Ariza, Lechuga, Pelegrina, & Bajo, 2005;Macrae & MacLeod, 1999;Phenix & Campbell, 2004), autobiographical memory (Barnier, Hung, & Conway, 2004;Harris, Sharman, Barnier, & Moulds, 2010), eyewitness memory (Garcia-Bajos, Migueles, & Anderson, 2009;MacLeod, 2002;Migueles & Garcia-Bajos, 2006;Shaw, Bjork, & Handal, 1995), visuo-spatial memory (Ciranni & Shimamura, 1999), and even memory for phonological information retrieved during language production (Levy, McVeigh, Marful, & Anderson, 2007). RIF, thus, is a general factor contributing to memory lapses in a broad range of contexts.…”
mentioning
confidence: 99%